Transient Global Amnesia Associated with an Acute Infarction at the Cingulate Gyrus - Alejandro Gallardo-Tur; Jorge Romero-Godoy; Carlos de la Cruz Cosme; Adriá Arboix (Case Reports in Neurological Medicine)
Background. Transient global amnesia (TGA) is a syndrome of sudden, unexplained isolated short-term memory loss. In the majority of TGA cases, no causes can be identified and neuroimaging, CSF studies and EEG are usually normal. We present a patient with TGA associated with a small acute infarct at the cingulate gyrus. Case Report. The patient, a 62 year-old man, developed two episodes of TGA. He had hypertension and hypercholesterolemia. He was found to have an acute ischemic stroke of small size (15 mm of maximal diameter) at the right cerebral cingulate gyrus diagnosed on brain magnetic resonance imaging. No lesions involving other limbic system structures such as thalamus, fornix, corpus callosum, or hippocampal structures were seen. The remainder of the examination was normal. Conclusion. Unilateral ischemic lesions of limbic system structures may result in TGA. We must bear in mind that TGA can be an associated clinical disorder of cingulate gyrus infarct.